Alumni assessment on the quality of services and curriculum relevance of Program Study Sports Science FIK UNY - Sigit Nugroho; Ahmad Nasrulloh; Sumaryanto Sumaryanto; Sumarjo Sumarjo; Duwi Kurnianto Pambudi (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2021)
This research is a quantitative descriptive study which aims to obtain an overview of alumni assessments in providing service quality and the relevance of the curriculum of the Sport Science Study Program, Faculty of Sport Sciences, Yogyakarta State University. The data collection method used a questionnaire with variables consisting of 1) the quality of financing services and academic activities 2) the waiting period of work, 3) the competence of graduates, and 4) the relevance of the curriculum. The population of this study were all graduates of the Ikor Study Program. Sampling with snowball sampling technique with a total of 113 samples. The research instrument used a questionnaire while for data collection techniques using google form. Data analysis was carried out by means of quantitative descriptive analysis. The results of the study show that the service quality of the Ikor study program in financing is very good, it is known that the tuition fees are 26.55% with scholarships and 73.45% at their own expense. Meanwhile, the quality of service in academic activities was good at 79.27%. Ikor Study Program graduates in obtaining employment amounted to 65.49% after graduating with an average of 3.47 months and before graduating 34.51% with an average of 5.23 months. The overall competence of graduates was very good, namely 85.3%, the most prominent being competence in working with teams or with other people, namely 88.5%. The results of the relevance of the curriculum are included in the very good category, namely 85.93%, in the relevance of the curriculum from the alumni assessment, the highest percentage of 90.97% was found in practice subjects that were delivered during lectures very well according to work needs. So as a whole it can be concluded that most of the alumni assessments in providing service quality and curriculum relevance are very good. PENILAIAN ALUMNI TERHADAP MUTU LAYANAN DAN RELEVANSI KURIKULUM PROGRAM STUDI ILMU KEOLAHRAGAAN FIK UNY AbstrakPenelitian ini merupakan penelitian deskriptif kuantitatif yang bertujuan untuk memperoleh gambaran tentang penilaian alumni dalam menyelenggarakan mutu layanan dan relevansi kurikulum Program Studi Ilmu Keolahragaan Fakultas Ilmu Keolahragaan Universitas Negeri Yogyakarta. Metode pengumpulan data menggunakan kuisioner dengan variabel yang terdiri dari 1) mutu layanan pembiayaan dan kegiatan akademik 2) masa tunggu pekerjaan, 3) kompetensi lulusan, dan 4) relevansi kurikulum. Populasi penelitian ini adalah seluruh lulusan Prodi Ikor. Pengambilan sampel dengan teknik snowball sampling dengan jumlah 113 sampel. Instrumen penelitian menggunakan kuisioner sedangkan untuk teknik pengumpulan data dengan google form. Analisis data dilakukan dengan jalan analisis deskriptif kuantitatif. Hasil penilitian menunjukan bahwa mutu layanan prodi Ikor dalam pembiayaan sangat baik, diketahui bahwa pembiayan kuliahnya sebesar 26,55 % dengan beasiswa dan sebesar 73,45 % dengan biaya sendiri. Sedangkan mutu layanan pada kegiatan akademik hasilnya baik yaitu sebesar 79,27 %. Lulusan Prodi Ikor dalam memperoleh pekerjaan sebesar 65,49 % sesudah lulus dengan rata-rata sebesar 3,47 bulan dan sebelum lulus sebesar 34,51 % dengan rata-rata sebesar 5,23 bulan. Kompetensi lulusan secara keseluruhan sangat baik yaitu 85,3 % yang paling menonjol kompetensi dalam bekerjasama dengan tim atau dengan orang lain yaitu sebesar 88,5 %. Hasil relevansi kurikulum masuk dalam kategori sangat baik yaitu sebesar 85,93 %, dalam relevansi kurikulum dari penilaian alumni persenstase yang paling tinggi yaitu sebesar 90,97 % terdapat pada matakuliah praktik yang disampaikan saat kuliah sangat sesuai dengan kebutuhan kerja. Sehingga secara keseluruhan dapat disimpulkan bahwa penilaian alumni dalam penyelenggaraan mutu layanan dan relevansi kurikulum sebagian besar menyatakan sangat baik.